2023
DOI: 10.1038/s41612-023-00403-5
|View full text |Cite
|
Sign up to set email alerts
|

How do North American weather regimes drive wind energy at the sub-seasonal to seasonal timescales?

Abstract: There has been an increasing need for forecasting power generation at the subseasonal to seasonal (S2S) timescales to support the operation, management, and planning of the wind-energy system. At the S2S timescales, atmospheric variability is largely related to recurrent and persistent weather patterns, referred to as weather regimes (WRs). In this study, we identify four WRs that influence wind resources over North America using a universal two-stage procedure approach. These WRs are responsible for large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…We consider the periods of March-May (MAM), June-August (JJA), September-November (SON), and December-February (DJF) to construct a training data set for each season. Choosing an appropriate number of SOM nodes to prescribe requires balancing the trade-off between distinctiveness and robustness (Liu et al, 2023;Liu et al, 2022;Huang et al, 2022). Song et al, (2019) found that clustering the convection associated weather patterns over the Great Plains using four nodes resulted in distinct large-scale environments while minimizing redundant nodes.…”
Section: Self-organizing Mapsmentioning
confidence: 99%
“…We consider the periods of March-May (MAM), June-August (JJA), September-November (SON), and December-February (DJF) to construct a training data set for each season. Choosing an appropriate number of SOM nodes to prescribe requires balancing the trade-off between distinctiveness and robustness (Liu et al, 2023;Liu et al, 2022;Huang et al, 2022). Song et al, (2019) found that clustering the convection associated weather patterns over the Great Plains using four nodes resulted in distinct large-scale environments while minimizing redundant nodes.…”
Section: Self-organizing Mapsmentioning
confidence: 99%